PENGARUH KUALITAS PRODUK, HARGA DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN SEPATU ONLINE DI TOKO L-IN SHOP BATAM - Tri Bambang; Indra Firdiyansyah (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2021)
This study aims to determine the effect of product quality, price and brand image on consumer purchasing decisions for fashion brands in Batam. The type of research used is descriptive verification by describing and explaining the variables studied and then drawing conclusions. The object of research that becomes the independent variable is product quality (X1), price (X2), brand image (X3) and purchase decision (Y) as the dependent variable. The population of this research is all consumers who buy shoes online at the Lin shop in Batam, which is 280 consumers. The sampling method used was accidental sampling, which is a sampling technique based on coincidence using the Slovin formula so that the sample in this study amounted to 74 people. The results showed the effect of product quality, price and brand image on purchasing decisions for fashion shoes in the city of Batam. R Square 21.5%. From these results it can be concluded that the Product Quality (X1), Price (X2) and Brand Image (X3) variables simultaneously influence the Purchasing Decision variable (Y) while 78.5% is influenced by other variables not examined in this study.